Beneficial Cardiovascular Effects of Hydroalcoholic Extract from Crocus Sativus in Hypertension Induced by Angiotensin II - Abdolali Faramarzi Plangar; Akbar Anaeigoudari; Abolfazl KhajaviRad; Mohammad Naser Shafei (Korean Pharmacopuncture Institute, 2019)
Objectives: Angiotensin II (AngII), a major product of renin-angiotensin system (RAS) has important role in induction of hypertension and antihypertensive effect of several medicinal plant was mediated by effect on this agent. Therefore, this study examined the possible effect of hydroalcoholic extract of Crocus sativus (C. sa tivus) on hypertension induced by AngII. Methods: Six groups (n = 6) of rats were used as follow: 1) Control, 2) AngII (300 ng/kg), 3) Losartan (Los, 10 mg/kg) + AngII and 4-6) C. sativus extract (10, 20 & 40 mg/kg,) + AngII. The femoral artery and vein were cannulated for recording cardiovascular parameters and drugs administration, respectively. All drugs were injected intravenously (i.v). Los and all doses of C. sativus injected 10 min before AngII. Systolic blood pressure (SBP), mean arterial blood pressure (MAP) and heart rate (HR) were recorded throughout the experiment and those peak changes (Δ) were calculated and compared to control and AngII. Results: AngII significantly increased ∆MAP, ∆SBP and ∆HR than control (P < 0. 01 to P < 0.001) and these increments were significantly attenuated by Los. All doses of C. sativus significantly reduced peak ΔMAP, ΔSBP, and ΔHR than AngII group (P < 0. 05 to P < 0.001). In addition, peak ΔMAP, ΔSBP in doses 10 and 20 were significant than Los + AngII group (P < 0.05 to P< 0.01) but in dose 40 only MAP was significant (P < 0.05). Peak ΔHR in all doses of C sativus was not significant than Los+ AngII. Conclusion: Regarding the improving effect of the C. sativus extract on AngII induced hypertension, it seems that this ameliorating effect partly mediated through inhibition of RAS.